Analysis of Students’ Thinking Level Based on SOLO Taxonomy in terms of Learning Style - Fitri Handayani; Alia Lestari; Sitti Zuhaerah Thalhah (Proceeding International Conference on Religion, Science and Education, 2023)
This study aims to determine the level of students’ thinking based on the SOLO taxonomy in solving math story problems in terms of Visual, Auditorial, and Kinesthetic (VAK) learning styles. This type of research is qualitative research with a descriptive approach. The VAK learning style questionnaire was given to thirty grade VIII.2 students of SMP Negeri 1 Tomoni to determine each student’s learning style. Then the researcher gave tests and interviews to one student from each type of learning style. The results showed that students with visual, auditory and kinesthetic learning styles had different levels of thinking in the SOLO Taxonomy. Based on the indicators of the level of thought in the SOLO Taxonomy, students with a visual learning style are at the uni-structural level, students with an auditory learning style are at the multi-structural level, and students with a kinesthetic learning style are at the relational level.